Raloxifene nano-micelles effect on triple-negative breast cancer is mediated through estrogen receptor-β and epidermal growth factor receptor. (14th September 2019) - Greish, Khaled; Nehoff, Hayley; Bahman, Fatemah; Pritchard, Tara; Taurin, Sebastien
Abstract: Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer that differs in progression, recurrence, and prognosis from other forms of breast cancer. The heterogeneity of TNBC has remained a challenge as no targeted therapy is currently available. Previously, we and others have demonstrated that raloxifene, a selective oestrogen receptor modulator, was also acting independently of the oestrogen receptor-α. However, raloxifene is characterised by a low bioavailability in vivo . Thus, we encapsulated raloxifene into a styrene-maleic acid (SMA) micelle to improve its pharmacokinetics. The micellar raloxifene had higher cytotoxicity when compared to the free formulation, promoted a higher cellular uptake and affected critical signalling pathways. Furthermore, SMA-raloxifene reduced TNBC tumour growth more efficiently than free raloxifene. Finally, we showed that this effect was partially mediated through oestrogen receptor-β. In conclusion, we have provided new insight into the role of raloxifene nanoformulation in improving the management of TNBC.